The key role of organic anion transporter 3 in the drug–drug interaction between tranilast and methotrexate. Issue 4 (12th January 2022) - Wang, Jingjing; Yuan, Wenjing; Shen, Qingqing; Wu, Qipeng; Jiang, Zhenzhou; Wu, Wei; Zhang, Luyong; Huang, Xin
Abstract: Tranilast, N‐(3′, 4′‐dimethoxycinnamoyl)‐anthranilic acid, is an anti‐allergic drug and is considered for use in the treatment of rheumatoid arthritis. Methotrexate, an antimetabolite and folate antagonist to treat some cancers, is also a first‐line drug for RA. The aim of this study was to understand whether tranilast could inhibit renal uptake transporters (Oat1, Oat3, and Oct2) and whether MTX combined with TL would have drug–drug interactions. The results of kidney slices and HEK293T‐OAT3 cell uptake experiments showed that TL (10 μM) could inhibit the uptake of penicillin G and MTX, which are substrates of OAT3. When TL (10 mg/kg) was combined with MTX (5 mg/kg), the area under the curve and peak concentration of MTX increased by 46.46% and 113.51%, respectively, while the pharmacokinetic process of tranilast (10 mg/kg) was not changed by methotrexate (5 mg/kg). TL could increase plasma exposure of MTX by inhibiting Oat3 in vitro and in vivo.